Three‐dimensional reconstruction of soybean nodules provides an update on vascular structure. Issue 3 (12th March 2019) - Livingston, David; Tuong, Tan; Nogueira, Marco; Sinclair, Thomas
Abstract : Premise of the Study: In many cases, the functioning of a biological system cannot be correctly understood if its physical anatomy is incorrectly described. Accurate knowledge of the anatomy of soybean [ Glycine max (L.) Merril] nodules and its connection with the root vasculature is important for understanding its function in supplying the plant with nitrogenous compounds. Previous two‐dimensional anatomical observations of soybean nodules led to the assumption that vascular bundles terminate within the cortex of the nodule and that a single vascular bundle connects the nodule to the root. We wanted to see whether these anatomical assumptions would be verified by digitally reconstructing soybean nodules in three dimensions. Methods: Nodules were dehydrated, embedded in paraffin, and cut into 15 μm thick sections. Over 200 serial sections were stained with safranin and fast green, and then photographed using light microscopy. Images were digitally cleared, aligned, and assembled into a three‐dimensional (3D) volume using the Adobe program After Effects. Key Results: In many cases, vascular bundles had a continuous connection around the nodules. The 3D reconstruction also revealed a dual vascular connection originating in the nodule and leading to the root in 22 of the 24 nodules. Of the 22 dual connections, 11 maintained two separate vascular bundles into the root with independent connections to the root vasculature. Conclusions: A more robust and complex anatomical pathway for vascular transport between nodules and root xylem in soybean plants is indicated by these observations and will contribute to a better understanding of the symbiotic relationship between soybean plants and nitrogen‐fixing bacteria within the nodules.